Pulsed Radiofrequency for Auriculotemporal Neuralgia: A Case Report - Yan Tereshko; Enrico Belgrado; Christian Lettieri; Simone Dal Bello; Giovanni Merlino; Gian Luigi Gigli; Mariarosaria Valente (MDPI AG, 2024)
Auriculotemporal neuralgia is a rare facial pain disorder with no therapeutic evidence for refractory cases. We described a male patient with right auriculotemporal neuralgia, refractory to anesthetic nerve blocks and botulinum toxin type A injections, who was successfully treated with pulsed radiofrequency without adverse events. Pulsed radiofrequency may be an effective and safe treatment for refractory auriculotemporal neuralgia.